Clinical and radiologic analysis of on-demand use of etanercept for disease flares in patients with rheumatoid arthritis for 2 years: The RESUME study. Issue 38 (September 2018) - Inui, Kentaro; Koike, Tatsuya; Tada, Masahiro; Sugioka, Yuko; Okano, Tadashi; Mamoto, Kenji; Sakawa, Akira; Fukushima, Kenzo; Nakamura, Hiroaki
Abstract : Abstract: To reduce costs of biological disease-modifying antirheumatic drugs (bDMARDs), we evaluated the efficacy of repeated etanercept (ETN) discontinuation and restarting in rheumatoid arthritis (RA) patients in a case–control study. Thirty-one bDMARD-naive RA patients with moderate to high disease activity received ETN until low disease activity (LDA) was achieved, after which ETN was discontinued. Upon flaring, ETN was readministered with observation every 2 months for 2 years, and radiographically evaluated in comparison with a historical control group treated continuously with ETN. Statistical methods including Fisher exact test, analysis of variance (ANOVA), Kruskal–Wallis test, multiple regression analysis, and Student t test were conducted as appropriate. Thirteen patients with inadequate response to ETN were withdrawn from the study, and 5 had no flare-up after ETN discontinuation. In the remaining 13 patients, ETN was used on-demand to maintain LDA. Multivariate analysis revealed that MTX was significantly correlated with ETN. All 13 patients achieved LDA at final follow-up. Although joint damage progressed in patients using ETN on-demand, structural damage progression in the on-demand group was not significantly different from that in controls. On-demand use of ETN for flaring reduced disease activity but not structural damage in 50% of patients (though not significantly). However, inhibition of joint damage was achieved in 50% of patients after 2 years, supporting on-demand use of ETN as a treatment option for patients with RA who cannot afford bDMARD or targeted synthetic DMARD therapy.